Complex Associations Between Systolic Left Atrial and Left Ventricular Deformations in Healthy Adults—Detailed Analysis from the Three-Dimensional Speckle-Tracking Echocardiographic MAGYAR-Healthy Study - Attila Nemes; Barbara Bordács; Nóra Ambrus; Csaba Lengyel (Life)
Introduction. Volumetric changes in the left atrium (LA) and left ventricle (LV) are strongly associated in healthy circumstances, as recent three-dimensional speckle-tracking echocardiographic (3DSTE) studies confirmed. However, the complex relationship of LA and LV deformation in systole has never been assessed in healthy individuals. The present study purposed to perform comparative simultaneous analysis of systolic LA and LV strains in healthy adults by 3DSTE. Methods. The study consisted of 165 healthy adults (mean age: 33.2 ± 12.3 years; 90 males). Complete two-dimensional Doppler echocardiography with 3DSTE was performed in all cases. Results. The increase in global LA radial strain (RS) and longitudinal strain (LS) showed no associations with LV strains. The largest global LA circumferential strain (CS) was associated with the largest basal LV-RS. Lowest basal and global LV-CS could be demonstrated in the presence of mean global LA-CS as compared to the presence of lower than mean global LA-CS. Global LA-RS showed an increase, with global LV-RS being largest when global LV-RS was the largest. Basal and global LA-RS were largest in the case of lowest global LV-CS. Basal LA-LS was largest in the case of mean global LV-CS. With the increase in global LV-LS, basal and global LA-LS showed an increase but only up to a point; in the case of larger than mean global LV-LS, no further increase was detected in basal and global LA-LS. Conclusions. Complex associations between simultaneously assessed LA and LV deformations represented by 3DSTE-derived strains could be demonstrated in healthy adults.